International Review of Applied Linguistics in Language Teaching (De Gruyter Mouton, 1963)
IRAL is devoted to problems of general and applied linguistics in their various forms. Its focus of interest lies in areas of research which concern first- and second-language acquisition (including sign language and gestural systems). Contributions cover topics such as naturalistic and instructed language learning, language loss, bilingualism, language contact, language for specific purposes, language technology and mother-tongue education.